Factoring food security: A Q Methodology study with Ghanaian educators - Jessica R. Spence; Tobin Redwine (Advancements in Agricultural Development)
Food security remains a pressing issue across sub-Saharan Africa, including Ghana. In response, education reform is essential for the country’s progress. This study unveils the perspectives of Ghanaian educators, recognizing their vital role in shaping the development, mindset, and actions of Ghanaian youth and contributing to SDGs 4 and 2, Quality Education and Zero Hunger. We employed Q methodology with the research aim of discovering the priorities and viewpoints of teachers regarding food insecurity. A sample of 31 Ghanaian educators, who previously or currently engaged with youth agricultural programming, participated in the Q-sort, sorting statements related to food insecurity. The analysis yielded four factor groups: Quality Over Quantity, Waste Not, Sustainable Sisters, and Futurists, each representing unique perspectives on addressing food security challenges. The findings affirm the importance of aligning education strategies with educators’ perspectives. We recommend tailored professional development opportunities to enhance awareness and effectiveness in addressing food insecurity issues. The study calls for further exploration of educator groups in Ghana, and the region, including qualitative investigations to inform targeted interventions and support the holistic development of youth engagement in addressing food security in Ghana.